DEVELOPING A MODIFIED REPERTORY GRID INSTRUMENT FOR ELICITING RESEARCH PARTICIPANT’S PERSONAL CONSTRUCTS (Universitas PGRI Sumatera Barat, 2014)
Previous application of the repertory grid technique in exploring participants’ personal constructs has been noteworthy. However, this technique could be modified to suit the purposes of the research questions, the conditions of the participants and the context of the study. This paper presents personal constructs theory which underpins the repertory grid technique and it also proposes the ways to developa modified repertory grid instrument for eliciting teachers’ personal constructs. According to Kelly (1955), a seminal psychologist, individual forms their constructs based on their observations and experiences and these personal constructs are used to interpret events. To elicit participants’ personal constructs regarding the topic under study, the repertory grid instrument, which is developed based on Kelly’s Personal Construct Theory, could bemodified through interview trials. After conducting the interview trials, the resultsshould be analyzed to identify whether this instrument is effective not only for participants but also for the researchers. The modified repertory grid instrument should allow and support participants in formalizing and elaborating their personal constructs. For the researchers, the instrument should be helpful to identify the participants’ personal constructs based on their own conceptions and understandings toward the topic under study.